Epidemiology of envenomation by Africanized honeybees in the state of Rio Grande do Norte, Northeastern Brazil - Michael Radan de Vasconcelos Marques; Kaliany Adja Medeiros de Araújo; Aluska Vieira Tavares; Alecxandro Alves Vieira; Renner de Souza Leite (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Introduction: In the American continent, accidents caused by honeybees are a public health problem due to the high incidence and severity of the cases. Despite its medical importance, there are few epidemiological studies on this topic in Brazil, especially referring to the Northeastern states. The present study aims to describe the epidemiological features of honeybee envenomation cases in the state of the Rio Grande do Norte, Northeastern Brazil, from 2007 to 2014. Methods: Data were collected from the Notifiable Diseases Information System database of the Health Department of Rio Grande do Norte. Results: We analyzed a total of 2,168 cases. Cases occurred in all months of the years studied, reaching higher frequencies from June to October. Most incidents happened in urban areas and involved men, with victims aged between 20 and 39 years. Victims were mainly stung on the head and hand, and they received medical care predominantly within 3 hours after the injury. Local manifestations were more frequent than systemic ones. Clinically, most cases were mild and progressed to cure. Conclusion: The high number of honeybee sting cases shows that Rio Grande do Norte may be an important risk area for such injury.